PENGARUH MEDIA SOSIAL INSTAGRAM TERHADAP PENJUALAN KAMAR DI BEVERLY HOTEL BATAM - Asikin, Nur; Pristiwasa, I Wayan Thariqy Kawakibi; Lubis, Arina Luthfini (Jurnal Pariwisata Budaya: Jurnal Ilmiah Pariwisata Agama dan Budaya, 2024)
Room sales at the Beverly Hotel Batam will increase and decrease in March 2023. Based on researchers' observations of the Beverly Hotel Batam, this hotel promotes its products via Instagram directly and can influence whether Beverly Hotel Batam followers and even other Instagram users can see what products are offered. Beverly Hotel Batam. The effectiveness and efficiency of marketing using Instagram media is still not visible in room sales. Quantitative research methodology was applied. Researchers used questionnaires as a data collection strategy. Descriptive statistical analysis is used to gain a general understanding of the social media variables Instagram (X) and room sales (Y). The mathematical formulation that shows the relationship between the two variables is Y = 5.082 + 0.770 Based on the research results, it was obtained that R Square = 0.491, which shows that the social media variable Instagram (X) contributed 49.1% to the Room Sales variable (Y), and the remaining 50.9% was influenced by variables not explored in this research. The results of this research provide input for hotels to pay more attention to selling their rooms which are displayed on Instagram social media, displaying prices, sharing photos and videos and creating content that attracts customers' attention.